1993
DOI: 10.1007/bf00053150
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for renal cell carcinoma: results of a population-based case-control study

Abstract: For a case-control study of risk factors for renal cell carcinoma, a mailed questionnaire was used to collect data on 518 cases and 1,381 population-based controls in Ontario, Canada. Active cigarette smoking increased risk twofold among males (odds ratio estimate [OR] = 2.0, 95 percent confidence interval (CI) = 1.4-2.8) and females (OR = 1.9, CI = 1.3-2.6). Passive smoking appeared to increase risk somewhat among nonsmokers (males: OR = 1.6, CI = 0.5-4.7; females: OR = 1.7, CI = 0.8-3.4). A high Quetelet ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
179
4
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(202 citation statements)
references
References 42 publications
18
179
4
1
Order By: Relevance
“…Compared to women with one or two births, multiparous women showed a more than two-fold risk increase, an association that was stronger among hypertensive or overweight women (Chow et al, 1995). In another study, a risk increase of similar magnitude was reported in multiparous women compared to nulliparous women, which was strictly limited to women with a previous history of foetal loss; among women with no foetal loss, the number of live Pregnancy and risk of renal cell cancer M Lambe et al births was unrelated to the risk of RCC (Kreiger et al, 1993). The latter study, as in our own, showed evidence of an inverse association between age at first birth and the risk of RCC.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Compared to women with one or two births, multiparous women showed a more than two-fold risk increase, an association that was stronger among hypertensive or overweight women (Chow et al, 1995). In another study, a risk increase of similar magnitude was reported in multiparous women compared to nulliparous women, which was strictly limited to women with a previous history of foetal loss; among women with no foetal loss, the number of live Pregnancy and risk of renal cell cancer M Lambe et al births was unrelated to the risk of RCC (Kreiger et al, 1993). The latter study, as in our own, showed evidence of an inverse association between age at first birth and the risk of RCC.…”
Section: Discussionmentioning
confidence: 82%
“…The influence of number of births on the risk of RCC remains unclear with a majority of studies finding no clear relation (Wynder et al, 1974;McLaughlin et al, 1984McLaughlin et al, , 1992Cantor et al, 1993;La Vecchia et al, 1993;Mellemgaard et al, 1994;GagoDominguez et al, 1999), while some investigators have reported positive associations (Kreiger et al, 1993;Chow et al, 1995;Lindblad et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous epidemiologic investigations of the association between use of paracetamol and cancer of the renal parenchyma (ie, renal cell cancer) have shown diverging results, 3,[5][6][7]13,15,17 and the weak associations identified in some of the studies may be explained by bias or uncontrolled confounding. 30 In a recent study of 1,204 matched case-control pairs, Gago-Dominguez et al 6 reported a significant odds ratio (OR) of 1.7 (95% CI, 1.3-2.1) for renal cell cancer associated with regular use of paracetamol, whereas McCredie et al, 3 in the largest study of this cancer to date, found no increase in risk of renal cell cancer among regular users of paracetamol (1,732 cases and 2,309 controls).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these have reported slightly elevated risks of renal cell cancer 2,5,6 or transitional cell cancers of the renal pelvis, ureter or urinary bladder 2,7-11 with regular or long-term use of paracetamol, whereas other studies have failed to demonstrate such associations. 3,5,7,[12][13][14][15][16][17][18] Few other cancer sites have been examined in relation to use of paracetamol. In a recent case-control study, Cramer et al 19 reported an inverse association between paracetamol use and risk of ovarian cancer.…”
mentioning
confidence: 99%